Study of the Application of Ecological Architecture in Housing on the Palm Oil Plantation of PT Agro Muara Rupit : Case Study of Remban, Rawas Ulu District, North Musi Rawas Regency, South Sumatra Province - Bayu Aulia Wahyudi Batubara; Dara Wisdianti; Melly Andriana (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
South Sumatra is a province with high natural resource potential in the palm oil plantation sector. The increasing demand for palm oil has led to many companies operating in this sector. One such plantation company is PT. Agro Muara Rupit, located in Rawas Ulu District, North Musi Rawas Regency, South Sumatra Province. This research is important because plantations are not only assessed from a commercial perspective, but must also have a positive impact on environmental sustainability. One environmentally conscious design concept is ecological architecture. Ecological architecture plays a role in protecting ecosystems from damage and creating comfort for residents from a physical, social, and economic perspective. This research aims to create environmentally conscious residential designs by applying ecological architecture concepts, ensuring the preservation of the natural environment. The research method used is a qualitative descriptive method with stages namely problem identification, data collection, analysis, and concept development, then the concept is implemented into the design. The results of this study are the implementation of four aspects of the ecological architecture concept in residential environments, including through natural ventilation and lighting systems by creating openings in the building, energy savings by using solar panels, the use of natural materials in the building mass such as clay, wood and bamboo, and the application of a bio pore system as water absorption.